Determination of forest biomass using remote sensing techniques with radar images. Pilot study in area of the province of Huelva. REDIAM - E. Méndez; J. J. Vales; I. Pino; L. Granado; G. Montoya; R. Prieto; I. R. Carpintero; F. Giménez de Azcárate; F. Cáceres; J. M. Moreira; D. de la Fuente; A. Sebastián; et al. (Revista de Teledetección)
Biomass is a very important forest resource in Andalusia. “Forest Biomass in Andalusia” web tool, developed by the Andalusian Government, provides information about the location and biomass stock for the main pine forest species. It is important to mention that information needs to be regularly, quickly, effectively and inexpensively updated. These requirements could be covered with the help of Earth Observation technologies. In this project, radar images have been acquired from ALOS-PALSAR sensor from different years (2008 and 2010) over two pilot areas located in Huelva. The aim of the study has been to develop a methodology to estimate wood volumes based on the statistic correlation between radar signal and wood volume, variable extracted of forest management plans contemporary to images. As result, correlations of 0.8 and 0.7 have been obtained for pine and eucalyptus respectively. Forest biomass has been calculated using species-specific allometric equations. Three key sources of information have been used: a sample of plots distributed homogeneously, an accurate digital terrain model and a current forest map. Furthermore, the study of the variability of estimated volumes between these dates has been carried out. Methodologies obtained could be extrapolated to the whole region.